2003
DOI: 10.1623/hysj.48.2.257.44693
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of streamflow and its components for a large Himalayan basin with predominant snowmelt yields

Abstract: A conceptual snowmelt model, which accounts for both the snowmelt and rainfall runoff was developed and applied for daily streamflow simulation for the Satluj River basin located in the western Himalayan region. The model, designed primarily for mountainous basins, conceptualizes the basin as a number of elevation zones depending upon the topographic relief. The basic inputs to the model are temperature, precipitation and snow-covered area. The snowmelt is computed using the degree-day approach and rain induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 12 publications
(10 reference statements)
1
55
0
Order By: Relevance
“…But the limited period of data (1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990) with 3 yr data missing) used in that study does not provide much statistical confidence. With an improved data network, more recent studies have simulated the "daily" flow of the Satluj River based on daily precipitation, temperature and snow cover information from the satellite images (Singh and Quick, 1993;Jain et al, 1998Jain et al, , 2010Singh and Jain, 2003). While these studies have reported better results with time, these conceptual rainfall-runoff models are not useful for longer-term (seasonal) forecasting since they are based on near-real-time daily weather data.…”
Section: Pal Et Al: Predictability Of Western Himalayan River Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…But the limited period of data (1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990) with 3 yr data missing) used in that study does not provide much statistical confidence. With an improved data network, more recent studies have simulated the "daily" flow of the Satluj River based on daily precipitation, temperature and snow cover information from the satellite images (Singh and Quick, 1993;Jain et al, 1998Jain et al, , 2010Singh and Jain, 2003). While these studies have reported better results with time, these conceptual rainfall-runoff models are not useful for longer-term (seasonal) forecasting since they are based on near-real-time daily weather data.…”
Section: Pal Et Al: Predictability Of Western Himalayan River Flowmentioning
confidence: 99%
“…The Spiti catchment (10 071 km 2 ) experiences extensive snowfall due to westerly weather disturbances in the winter months that contribute to the Satluj flow in spring, or in MAMJ (Singh and Kumar, 1997), which is of our interest. In general the maximum snow cover area exists in March, by when most of the snowfall has occurred (Singh and Jain, 2003).…”
Section: Study Region and Datamentioning
confidence: 99%
“…Therefore, bearing this in mind, SNOWMOD was developed using a temperature index approach. Details of the model may be found in Singh & Jain (2003) and the flow chart of the model structure is shown in Fig. 2.…”
Section: Special Features Of the Snowmelt Model (Snowmod)mentioning
confidence: 99%
“…Several other field studies have determined the temperature lapse rates for mountainous regions of the world in the range of 0.5-0.7ºC/100 m (Pielke & Mehring, 1977;Barry, 1992;de Scally, 1997;Singh & Singh, 2001;Singh & Jain, 2002;Singh & Jain, 2003;Thayyen, 2003). For the Himalayan basins, temperatures were lapsed at 0.60ºC/100 m to the mean hypsometric elevation of different elevation zones for melt computation (Singh & Jain, 2002) and such a lapse rate was used in the present study.…”
Section: Meteorological Data Precipitationmentioning
confidence: 99%
“…Thus, RS is an indispensable tool for simulating and/or forecasting of snowmelt runoff and climate studies by the snowcovered area analysis it offers. A review of RS in snow hydrology is given by Rango (1993) and some applications are presented in Akyürek & Sorman (2002), Singh & Jain (2003), Bernier et al (2003), Shaban et al (2004), and Aouad-Rizk et al (2005). Even though RS enables the determination of SCA on a daily basis, there may exist some missing dates in the determination of SCA, due either to the cost involved for image analysis or to the time duration required for satellite image processing.…”
Section: Introductionmentioning
confidence: 99%